تأثير وسيلة الدمية التعليمية في تعليم مهارة الكلام لطلاب الفصل الحادى عشر بالمدرسة الثانوية معهد دار الفنون العباسية بادنج جافنج - Husana, Ana Alif; Husni, Arman; Dewi, Yelfi; Rizal, Eka (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Ana Alif Husana (1127222) : The Influence of educative leather puppet in learning of Arabic Speech Proficiency at The Eleventh Grade of Darul Funun El Abbassyiyah Islamic Hish School Padang Japang. The fundamental issue in learning of Arabic Speech Proficiency in Darul Funun El Abbassiyah Islamic High School Padang Japang is there was a lack of learning tool of Arabic lesson especially in Speech Proficiency or commonly known as Maharh Kalam. The students were less trained and often feeling shy when they speak Arabic. Thus, the researcher used a learning media to improve the students speaking skill in Arabic by used an educative leather puppet or commonly known as Wayang. The purpose of using this media was to help the students to practice their speaking in Arabic and make the learning process become interesting for students and also teacher. The method used by researcher was experimental which involved an experimental class and control class. The type of this research was quantitative design. The learning outcome of Arabic specch proficiency after using this media showed that the mean score of final test in experimental class was 707. While the mean score in control class was 71,26. The researcher analyze the result of hypothesis test using independent t-test and found that the score (sig-tailed) was 2,221 which was lower than 2,20. It can be concluded that, there was a significant possibilities that the the use of educative towards the learning of Arabic Specch Proficiency at the eleventh grade of Darul Funun El Abbassiyah Islamic High School Padang Japang.